Impact of two mycotoxins deoxynivalenol and fumonisin on pig intestinal health - ALASSANE-KPEMBI, IMOURANA (My University, 2016)
Mycotoxins are secondary metabolites of fungi that grow on a variety of substrates. Due to their high consumption of cereals and their sensitivity, pigs are highly impacted by the presence of mycotoxins. At the European level, regulations and recommendations exist for several mycotoxins in pig feed. Among these toxins, fumonisin B1 (FB1), and deoxynivalenol (DON) have a great impact on the intestine and the immune system. Indeed, the intestine is the first barrier to food contaminants and can be exposed to high concentrations of mycotoxins upon ingestion of contaminated feed. FB1 and DON alter the intestinal barrier, impair the immune response, reduce feed intake and weight gain. Their presence in feed increases the translocation of bacteria; mycotoxins can also impair the immune response and enhance the susceptibility to infectious diseases. In conclusion, because of their effect on the intestine, FB1 and DON are a major threat to pig health, welfare and performance.
Keywords: Barrier function; Deoxynivalenol; Feed contamination; Fumonisin B1; Immune response; Intestine; Pig